발목 관절염에서 체중부하 전산화 단층촬영의 활용 - 조재호; Otgonsaikhan Nomkhondorj; Jaeho Cho (대한족부족관절학회지, 2025)
Weight-bearing computed tomography (WBCT) is an advanced imaging modality that allows for a three-dimensional assessment of the foot and ankle under a physiological load. It overcomes the limitations of traditional radiographs and non-weight-bearing CT/MRI by providing a more precise evaluation of the joint space narrowing, malalignment, and dynamic changes associated with ankle arthritis. Recent studies have shown the advantages of WBCT in classifying ankle arthritis, revealing previously unrecognized deformities such as valgus tilting in medial gutter arthritis. WBCT also enhances the diagnostic accuracy by quantifying talar rotation, hindfoot alignment, and subtalar joint compensation, which are critical for treatment planning. In addition, WBCT has proven useful in surgical applications, including supramalleolar osteotomy and total ankle arthroplasty, by aiding in preoperative planning, patient-specific instrumentation, and postoperative assessments. It also enables the early detection of complications such as implant malalignment and periprosthetic osteolysis. As WBCT technology continues to evolve, WBCT is expected to play a growing role in optimizing the diagnostic precision and improving treatment outcomes for ankle arthritis. Future research should focus on standardizing WBCT-based measurements and integrating quantitative analysis to enhance clinical decision-making.